2014
DOI: 10.1111/brv.12130
|View full text |Cite
|
Sign up to set email alerts
|

Topographic determinants of mobile vertebrate predator hotspots: current knowledge and future directions

Abstract: Despite being identified as a driver of mobile predator aggregations (hotspots) in both marine and terrestrial environments, topographic complexity has long remained a challenging concept for scientists to visualise and a difficult parameter to estimate. It is only with the advent of high-speed computers and the recent popularisation of geographical information systems (GIS) that terrain attributes have begun to be quantitatively measured in three-dimensional space and related to wildlife dynamics, making the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
105
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 228 publications
(223 reference statements)
1
105
0
Order By: Relevance
“…Many different terrain attribute selections have been used in terrestrial and marine ecology ([1,7]; references therein). In a meta-analysis of ecological studies using geomorphometry, Bouchet et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many different terrain attribute selections have been used in terrestrial and marine ecology ([1,7]; references therein). In a meta-analysis of ecological studies using geomorphometry, Bouchet et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of ecological studies using geomorphometry, Bouchet et al . [1] found that about a third of the studies only used one terrain attribute and that very few authors used more than four. While focusing on forest ecosystems, Sharaya & Sharyi [40] wrote that in general, one to three basic terrain attributes are used to study landscape phenomena and that the “insufficient representativeness” ( ibid , p. 2) of terrain attributes makes for an inefficient use of topography as a variable in ecology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, topographically complex landscapes such as the shelf break and areas near the Chun Spur may lead to spatially localized and stable micro-niches in terms of oceanography and associated prey resources (Bouchet et al, 2014). Such conditions may allow for shorter search times for prey patches, and therefore increase foraging profitability in terms of CPUE on the foraging trip scale.…”
Section: Importance Of Bathymetry-related Oceanographic Processesmentioning
confidence: 99%
“…Collecting biological data over broad spatial scales is often time consuming and expensive, resulting in the use of abiotic surrogates, such as terrain attributes, to associate with habitat classes for extrapolation [12,23]. Bathymetry and backscatter are the primary products of acoustic sampling providing full coverage data of the seafloor.…”
Section: Introductionmentioning
confidence: 99%